2001
DOI: 10.1096/fj.00-0721fje
|View full text |Cite
|
Sign up to set email alerts
|

Selenium deficiency increases the pathology of an influenza virus infection

Abstract: Selenium (Se) deficiency has previously been shown to induce myocarditis in mice infected with a benign strain of coxsackievirus. To determine if Se deficiency would also intensify an infection with influenza virus, Se‐deficient and Se‐adequate mice were infected with a mild strain of influenza, influenza A/Bangkok/1/79 (H3N2). Infected Se‐deficient mice developed much more severe interstitial pneumonitis than did Se‐adequate mice. This increase in pathology was associated with significant alterations in mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
211
1
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(224 citation statements)
references
References 42 publications
6
211
1
6
Order By: Relevance
“…However, antibody titers to poliovirus were not affected by levels of Se intake, thus suggesting that plasma B cell production of IgG was not affected by Se supplementation. Consistent with this notion, rodent studies described in detail next involving influenza infection also showed no significant effect of increasing dietary Se on humoral responses (18). In a very small study involving 11 men, antibody titers against diphteria vaccine, but not against influenza A or B, were increased after reinoculation in high Sesupplemented (297 lg/day) versus low Se-supplemented (13 lg/day) individuals (95).…”
Section: B B Cell Function and Antibody Productionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, antibody titers to poliovirus were not affected by levels of Se intake, thus suggesting that plasma B cell production of IgG was not affected by Se supplementation. Consistent with this notion, rodent studies described in detail next involving influenza infection also showed no significant effect of increasing dietary Se on humoral responses (18). In a very small study involving 11 men, antibody titers against diphteria vaccine, but not against influenza A or B, were increased after reinoculation in high Sesupplemented (297 lg/day) versus low Se-supplemented (13 lg/day) individuals (95).…”
Section: B B Cell Function and Antibody Productionmentioning
confidence: 66%
“…Influenza viruses. Studies comparing Se-deficient to Se-sufficient mice infected with influenza A virus [Influenza A/Bangkok/1/79 (H3N2)] demonstrated the importance of adequate Se intake for viral clearance and recovery (18). Viral titers were similar between Se-deficient and Se-sufficient hosts.…”
Section: Linkages Between Se and Human Diseasementioning
confidence: 99%
“…Se-deficient mice exhibit increased pathology from viral infection, owing to an exaggerated pro-inflammatory immune response. 204,205 Se deficiency or deletion of GPx1 in mice also increases viral mutations and virulence. 206 Accordingly from these functions, it is expected that Se carries out beneficial effects on inflammatory conditions.…”
Section: Immune Defence and Inflammatory Disordersmentioning
confidence: 99%
“…That adequate selenium is required for protection against viral infection has been demonstrated by Beck (1997) and Beck and Levander (2000), who suggest that nutritional deprivation may be one of many factors that increase the susceptibility of individuals to influenza infection (Beck et al, 2001). There is insufficient data, particularly in human subjects, to estimate an optimal dietary intake or an optimal plasma selenium concentration for protection against viral infection.…”
Section: Blood Selenium Concentrations Above Which Keshan Disease Ismentioning
confidence: 99%